Factors affecting export competitiveness of fisheries industry in Malaysia - Soh, Bee Hui; Lim, Ghee-Thean; Chua, Soo Y. (Journal of Fisheries, 2025)
Fisheries constitute the most highly traded food commodity internationally owing to its fundamental contribution to global food security and nutrition. Malaysia has been amongst the world’s leading fish producers; however, it has faced a serious fish trade deficit, implicating an absence of export competitiveness in the industry. This study aims to measure the export competitiveness (i.e. Comparative Export Performance index, CEP) of the industry and examine factors affecting CEP by adopting the Autoregressive Distributed Lag (ARDL) approach on the time series data for 2001 – 2022. The major findings revealed that Malaysia recorded an absence of export competitiveness (i.e. CEP < 0) in the international fisheries market, and this issue was significantly affected by fish consumption, followed by foreign income and fisheries production. Fisheries production and foreign income positively affected the CEP in the short-run while fish consumption negatively affected it. In the long-run, fish consumption and foreign income exerted a negative effect on the CEP. The findings of this study are significant for understanding the short- and long-run effects on export competitiveness in Malaysia and can be used for fisheries development strategies.